2002
DOI: 10.1037/0735-7044.116.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced conditioned taste aversion in 15 inbred mouse strains.

Abstract: This study used a genetic correlational strategy to characterize the neurobiological basis of ethanol's (0, 2, or 4 g/kg) aversive effects as indexed by conditioned taste aversion. Substantial strain differences in taste aversion and hypothermia were observed, but the genetic correlation between these phenotypes was not significant. However, significant genetic correlations were observed between taste aversion and ethanol-related behaviors measured in previous studies, including home-cage ethanol preference (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
122
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 48 publications
21
122
0
4
Order By: Relevance
“…This genetic correlation (r = 0.623, n=13; p < 0.05) agreed strongly with previously published correlations between CTA at 2 g/kg and ethanol preference (Belknap et al, 1993;Broadbent et al, 2002). This association between CTA and drinking supports the finding of such an association in both the quantitative and qualitative meta-analyses described above.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This genetic correlation (r = 0.623, n=13; p < 0.05) agreed strongly with previously published correlations between CTA at 2 g/kg and ethanol preference (Belknap et al, 1993;Broadbent et al, 2002). This association between CTA and drinking supports the finding of such an association in both the quantitative and qualitative meta-analyses described above.…”
Section: Resultssupporting
confidence: 91%
“…We found that higher home cage alcohol drinking associates with lower CTA, agreeing with previous findings that strains of mice which show stronger taste aversion also tend to show lower ethanol preference and higher withdrawal severity (Broadbent et al, 2002). Such results suggest that with respect to ethanol, CTA reflects the likelihood of animals to acquire an aversion to flavors (including ethanol itself) paired with ethanol's actions, an effect that interferes with drinking behavior.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, aversive effects of the drug are easily found by pairing a novel flavor or distinctive place with the post absorptive effects of EtOH. Animals will later exhibit strong taste or place avoidance, particularly when a high dose of EtOH is employed (Broadbent et al, 2002;Fidler et al, 2004;Pautassi et al, 2002). …”
Section: Introductionmentioning
confidence: 99%